Non-small cell carcinoma-not otherwise specified on cytology specimens in patients with solitary pulmonary lesion: Primary lung cancer or metastatic cancer? - Hyoun Wook Lee; Seung Yeon Ha; Mee Sook Roh (Journal of Cytology, 2021)
Context: Subtyping of solitary pulmonary lesion (SPL) in small amount of cytology specimen using a limited panel of immunohistochemistry (IHC) markers is very important to the correct choice of treatment. This study was performed to categorize non-small cell carcinoma-not otherwise specified (NSCC-NOS) on cytology in patients with SPL, especially with regard to the incidence of metastatic cancer. Materials and Methods: We reviewed 91 cases, in which a precise morphology-based, lineage-specific IHC-aided subtyping was not possible, that qualified as NSCC-NOS on cytology. A stepwise clinical approach and IHC of organ-specific markers was performed on each cell block (CB) to exclude metastasis from extrapulmonary malignancies. Results: Of the 91 evaluated cases, 65 (71.4%) were diagnosed as non-small cell lung carcinoma (NSCLC)-NOS, 24 (26.4%) were metastatic cancer, and the remaining 2 (2.2%) had undetermined diagnoses. The most frequent primary tumor site was the colorectum (41.7%), followed by breast (20.8%), kidney (8.3%), and then stomach, duodenum, liver, pancreas, gallbladder, prostate, and skin (4.2% each, 1 of 24). Moreover, we found that 7 of the 24 patients with metastatic cancer had a history of extrapulmonary malignancy that was unknown at the time of cytology-based diagnosis. Conclusions: These results underscored the need for accurate and stepwise clinical correlation to rule out the possibility of pulmonary metastasis from other sites and appropriate but judicious IHC (i.e., CDX2) on CB for SPL to increase refinement of the cytology diagnosis of NSCC-NOS.